SPORTS TRAINING FOR 16-17 YEARS OLD SKIERS-RACERS IN MID-MOUNTAIN CONDITIONS - Bezmaternykh, I.S.; Gorbunov, S.S.; Kostareva, S.V.; Ibragimov, R.R. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to determine the effectiveness of various approaches to the organization of the training process of 16-17 year old ski-racers in the competitive period in mid-mountain conditions. Methods and structure of the study. The experiment involved two groups of young men with the 1st sports category, and a candidate for master of sports. The experimental group used the traditional approach with the inclusion of two cycles - adaptation and transition. The peculiarity of the organization of the training process was a gradual increase in the volume of low-intensity load against the background of monitoring adaptive-compensatory mechanisms and an increase in the intensity of the load by a repeated and variable method against the background of a reduced volume by the end of the cycle. The control group used a block approach, the features of which were the inclusion of a block of foothill training and the use of two peaks of high intensity in a weekly microcycle when training in the mountains, using the interval method against the background of underrecovery. Results and conclusions. The results of the experimental group in all priority functional indicators significantly exceeded the results of the control group. A significant increase in the results in the 7.5 km race occurred in both groups and was almost the same. At the same time, it should be taken into account that the athletes of the control group used more stringent work regimes. This confirms the forcing of training, which, in our opinion, is unacceptable in these conditions for athletes of this age.